Serum Homer1 is a Novel Biomarker for Predicting the Clinical Outcomes of Acute Ischemic Stroke Patients - Lv W; Ruan Z; Zhang Q; Wei Y; Wu X; Dou YN; Chao W; Fei X; Fei Z (Dove Medical Press, 2024)
Weihao Lv,1,* Zhe Ruan,2,* Qianqian Zhang,3,* Yaxuan Wei,4,* Xiuquan Wu,1 Ya-Nan Dou,1 Wangshu Chao,1 Xiaowei Fei,1 Zhou Fei1 1Department of Neurosurgery, Xijing Hospital, Air Force Medical University, Xi'an, Shaanxi, 710032, People's Republic of China; 2Department of Neurology, Tangdu Hospital, Air Force Medical University, Xi'an, Shaanxi, 710032, People's Republic of China; 3Department of Respiratory Medicine, Lanzhou University Second Hospital, Lanzhou, 730070, People's Republic of China; 4Department of Neurology, Gansu Province Central Hospital, Lanzhou, 730070, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaowei Fei; Zhou Fei, Xijing Hospital, Air Force Medical University, No. 127, Changle West Road, Xincheng District, Shaanxi, 710032, People's Republic of China, Tel +86-1882928538, Email xiaowei_fei@fmmu.edu.cn; feizhou@fmmu.edu.cnPurpose: We aim to explore the relationship between Homer1 and the outcomes of AIS patients at 3 months.Patients and Methods: This prospective cohort study was conducted from May 2022 to March 2023. In this study, we investigated the association between serum Homer1 levels by enzyme-linked immunosorbent assay at admission and functional outcomes of patients at 3 months after AIS.Results: Overall, 89 AIS patients (48 good outcomes and 41 poor outcomes) and 83 healthy controls were included. The median serum Homer1 level of patients at admission with poor outcomes was significantly higher than that of patients with good outcomes (39.33 vs 33.15, P< 0.001). Serum Homer1 levels at admission were positively correlated with the severity of AIS (r = 0.488, P< 0.001). The optimal cutoff of serum Homer1 level as an indicator for an auxiliary diagnosis of 3 months functional outcomes was 35.07 pg/mL, with a sensitivity of 75.0% and a specificity of 92.7% (AUC 0.837; 95% CI [0.744- 0.907]; P< 0 0.001). The odds ratio of MRS > 2 predicted by the level of serum Homer1 after 3 months was 1.665 (1.306- 2.122; P< 0.001).Conclusion: Serum concentrations of Homer1 have a high predictive value for neurobehavioral outcomes after acute ischemic stroke. Higher serum Homer1 levels (> 35.07 pg/mL) were positively associated with poor functional outcomes of patients 3 months post-stroke.Keywords: Homer1, acute ischemic stroke, biomarker, outcomes